GOALS OF TEACHING ENGLISH (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article examines the main goals of teaching English as a foreign language in modern educational contexts. English, being a global lingua franca, plays a crucial role in communication, science, technology, and cultural exchange. The study identifies cognitive, communicative, cultural, and professional objectives in English language instruction and analyzes teaching strategies that help achieve these goals. Findings indicate that goal-oriented instruction contributes to learners’ linguistic competence, intercultural awareness, and practical skills required for academic and professional success.